Law and ethnic plurality : socio-legal perspectives - Shah, Prakash (Immigration and asylum law and policy in Europe, 2007)
The large-scale establishment of ethnic minorities and diasporic communities in Europe has gained the attention of social science scholars for a number of decades now. However, legal interest in this field has remained relatively underdeveloped.